Hand Hygiene With Alcohol-Based Hand Rub: How Long Is Long Enough?. (7th March 2017) - Pires, Daniela; Soule, Hervé; Bellissimo-Rodrigues, Fernando; Gayet-Ageron, Angèle; Pittet, Didier
Abstract : BACKGROUND: Hand hygiene is the core element of infection prevention and control. The optimal hand-hygiene gesture, however, remains poorly defined. OBJECTIVE: We aimed to evaluate the influence of hand-rubbing duration on the reduction of bacterial counts on the hands of healthcare personnel (HCP). METHODS: We performed an experimental study based on the European Norm 1500. Hand rubbing was performed for 10, 15, 20, 30, 45, or 60 seconds, according to the WHO technique using 3 mL alcohol-based hand rub. Hand contamination with E. coli ATCC 10536 was followed by hand rubbing and sampling. A generalized linear mixed model with a random effect on the subject adjusted for hand size and gender was used to analyze the reduction in bacterial counts after each hand-rubbing action. In addition, hand-rubbing durations of 15 and 30 seconds were compared to assert non-inferiority (0.6 log10 ). RESULTS: In total, 32 HCP performed 123 trials. All durations of hand rubbing led to significant reductions in bacterial counts ( P <.001). Reductions achieved after 10, 15, or 20 seconds of hand rubbing were not significantly different from those obtained after 30 seconds. The mean bacterial reduction after 15 seconds of hand rubbing was 0.11 log10 lower (95% CI, −0.46 to 0.24) than after 30 seconds, demonstrating non-inferiority. CONCLUSIONS: Hand rubbing for 15 seconds was not inferior to 30 seconds in reducing bacterial counts on hands under the described experimental conditions. There was no gain in reducing bacterial counts from hand rubbing longer than 30 seconds. Further studies are needed to assess the clinical significance of our findings. Infect Control Hosp Epidemiol 2017;38:547–552